Typology of opening scenes in the new generation of TV series - Borowiecki, Artur (Kultura-Społeczeństwo-Edukacja, 2021)
The product of quality TV, modern TV series have undergone significant changes compared to traditional productions. TV series used to have a closed episodic structure, contained within a single episode. These days, the format marked by a narrative continuity prevails. The types of sequences that open TV series have changed, too. Filmmakers employ various ‘opening strategies’ to make their productions stand out and attract audiences’ attention. The initial scenes highlight dynamic action, set the tone and express the central conflict. Other types of opening aim to explicate the main protagonist to make them intriguing. This article will provide the definition of ‘opening scenes’, and their typology will be discussed based on selected examples.